Psychosocial consequences of screening-detected abdominal aortic aneurisms: a cross-sectional study - Christina Sadolin Damhus; Volkert Siersma; Anders Hansson; Christine Winther Bang; John Brodersen (Taylor & Francis Group, 2021)
Objective In Sweden, an abdominal aortic aneurysm (AAA) screening programme was gradually implemented from 2009 to reduce the incidence of rupture and thereby mortality. AAA screening introduces a variety of unintended, but generally unavoidable, harms, e.g. stress and worry. Such psychosocial consequences have previously only been investigated with generic measures. Therefore, the aim of this study was to describe and compare the psychosocial consequences in men with a screening detected AAA to men with a normal screening result after they participated in the Swedish national AAA-screening programme using a validated psychometric instrument. Material and methods This study was a cross-sectional survey. Data were originally collected to validate the COS-AAA and has previously been published in details. The Consequences of Screening in Abdominal Aortic Aneurysm (COS-AAA) questionnaire was sent to 250 men with a screening detected AAA and 500 with a normal screening result who were randomly selected from a Swedish population-based screening register. Results In total, 158 (63%) men with a screening detected AAA and 275 (55%) men with a normal screening result completed the COS-AAA. We found that men with a screening detected AAA reported negative psychosocial consequences to a greater extent in 10 of 13 COS-AAA Part 1 scales, all statistically significant except three (behaviour, sleep and negative experiences from examination). For COS-AAA Part 2, there was a statistically significant difference between groups in four of five scales. Conclusions Men diagnosed with a screening detected AAA, reported more negative psychosocial consequences compared to men with a normal result. Screening for abdominal aorta aneurism (AAA) introduces intended benefits and unintended harms. Adequate measures are necessary to determine the balance between them.Key points: This study applied a condition-specific questionnaire with high content validity and adequate psychometric properties to measure psychosocial consequences in men participating in AAA screening. We found that men with a screening detected AAA reported more negative psychosocial consequences than men with a normal aorta size. The risk of negative psychosocial consequences is important to include in the decision making on whether to participate in screening or not.